PENGARUH LATIHAN KNEE TUCK JUMP TERHADAP POWER OTOT TUNGKAI PADA SISWI EKSTRAKURIKULER BOLA VOLY PUTRI SMA N 11 PEKANBARU - M.Farid '; Ramadi '; Ni putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research it still a lack of explosive power of leg muscle when they smash and block in student extracurricular volleyball women’s SMA N 11 pekanbaru.based on the researchers training provide Knee Tuck Jump. The research to determine whether there is effect Reactive Jump Over Hurdles exercises to the leg muscle of explosive power of student extracurricular volleyball women’s sma n 11 pekanbaru, so that when a jump smash and block to get the maximum lea. This research is the experimental treatment (Experimental), with a population of student extracurricular volleyball women’s SMA N 11 pekanbaru, the data in this research is the entire population of 14 people. The instruments used in this research is Vertical Jump Test, which aims to measure the explosive power leg muscle. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect Knee Tuck Jump exercises to the explosive muscle power. Based on the analysis of statistical data, there are an average Pree-test of 31,14 and an average post-test 32,64, then the data is normal with an increase of 1,22. Based on the test analysis produces Ttabel = 1,771and Thitung =3,66, meaning Thitung> Ttabel. Thus, there Effect of Exercise Knee Tuck Jump on Explosive Power on a Leg Muscle student extracurricular volleyball women’s SMA N 11 pekanbaruKeywords : Knee Tuck Jump, the explosive muscle power.